LTBK-08. TOCA 511 & TOCA FC VERSUS STANDARD OF CARE IN PATIENTS WITH RECURRENT HIGH GRADE GLIOMA. (22nd November 2019) - Cloughesy, Timothy; Petrecca, Kevin; Walbert, Tobias; Butowski, Nicholas; Salacz, Michael; Perry, James; Damek, Denise; Bota, Daniela; Bettegowda, Chetan; Zhu, Jay-Jiguang; Iwamoto, Fabio; Placantonakis, Dimitris; et al.
Abstract: BACKGROUND: Toca 511 (vocimagene amiretrorepvec) is a cancer-selective, retroviral replicating vector encoding a codon optimized, heat stabilized cytosine deaminase that converts Toca FC (extended-release 5-fluorocytosine, 5-FC) into the anticancer agent 5-fluorouracil. Three Ph1 studies in patients with recurrent high grade glioma have demonstrated a tolerable safety profile and encouraging efficacy. METHODS: Toca 5 is a multi-national, randomized, open-label Ph3 trial (NCT02414165) of Toca 511 & Toca FC versus standard of care (SOC) options that comprises Investigator's choice of single agent chemotherapy (lomustine, temozolomide) or bevacizumab in patients who have undergone resection for first or second recurrence of glioblastoma or anaplastic astrocytoma. 403 patients were randomized 1:1 to the Toca arm or the SOC arm and stratified by IDH1 status, KPS, and geographic region. Primary endpoint was overall survival (OS), and secondary endpoints were durable response rate, durable clinical benefit rate, duration of durable response, and 12-month survival rate. The study used group sequential design including 2 interim analyses and 1 final analysis, and the stratified log-rank test are used for the analysis. RESULTS: 271 events were observed for this analysis. Median follow-up was 22.8 months, and the Toca arm missed the primary endpoint (OS) compared to the SOC arm (11.1 months median compared to 12.2 months, HR=1.06, p=0.6154). All secondary endpoints showed no meaningful difference between the arms of the trial. The safety, tolerability and adverse event profile of Toca 511 and Toca FC was as expected for this patient population, with low incidences of Grade 3–4 adverse events. Pre-planned subgroup analyses showed compelling OS improvement in patients with secondary recurrence, and favorable trends in IDH1 mutant and AA population. Detailed data will be presented at the time of the conference.